Dopamine Suppresses Synaptic Responses of Fan Cells in the Lateral Entorhinal Cortex to Olfactory Bulb Input in Mice - Liu, Shaolin (Frontiers in Cellular Neuroscience, 2020)
The lateral entorhinal cortex (LEC) is involved in odor discrimination, odor-associative multimodal memory, and neurological or neuropsychiatric disorders. It receives direct axonal projections from both olfactory bulb (OB) output neurons and midbrain dopaminergic neurons. However, the cellular targets in LEC receiving direct synaptic input from OB output neuron, the functional characteristics of these synapses, and whether or how dopamine (DA) modulates the OB-LEC pathway remain undetermined. We addressed these questions in the present study by combing optogenetic and electrophysiological approaches with four major findings: (1) selective activation of OB input elicited glutamate-mediated monosynaptic responses in all fan cells, the major output neurons in layer II of the LEC; (2) this excitatory synaptic transmission exhibited robust paired-pulse facilitation (PPF), a presynaptically derived short-term synaptic plasticity; (3) DA dramatically attenuated the strength of the OB input-fan cell synaptic transmission via activation of D1 receptors; (4) DA altered the PPF of this transmission but neither intrinsic properties of postsynaptic neurons nor the kinetic profile of postsynaptic responses, suggesting that presynaptic mechanisms underlie the DA inhibitory actions. This study for the first time demonstrates the FCs in the LEC layer II as the postsynaptic target of direct OB input and characterizes DA modulation of the OB input-fan cell pathway. These findings set the foundation for future studies to examine the synaptic transmission from the OB output neuron axon terminals to other potential cell types in the LEC and to pinpoint the pathophysiological mechanisms underlying olfactory deficits associated with DA-relevant neurological and neuropsychiatric disorders.